APPLIED ASPECTS OF SUSTAINABLE DEVELOPMENT OF ECONOMIC ENTITIES IN MODERN DIFFICULT ECONOMIC CONDITIONS - Schneider, O.V (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The purpose of the research is the applied aspects of sustainable development of business entities in today's difficult economic conditions. Preliminary analysis of the factors influencing the level of sustainable development of business entities determines the importance of economic justification of this complex process. The reflection of the performance of any business entity through the acceptance of economic, environmental and social indicators, concluded in the values of financial and non-financial indicators contributes to the assessment of the level of sustainable development. The implementation of this task is due to the study and generalization of theoretical knowledge and practical skills that allow to develop existing methods of analysis of sustainable development of business entities. The result of the analytical study is based on the substantiation of specific proposals for the economic justification of the sustainability of economic entities. The scientific novelty of the study is to develop a method of economic justification of sustainable development of business entities in the current crisis conditions. To determine the level of sustainable development of business entities identified tools for the implementation of the development strategy of the business entity. The main stages of cyclical management of sustainable development of a business entity are outlined. The analysis of the relationship between the strategic directions of a balanced scorecard. The result of the study allowed to suggest the directions of sustainable development of business entities in terms of the balance of economic, social and environmental factors.